Perkembangan Sistem Pendidikan di Inggris - Nur Sakinah Siregar; Mislaini Mislaini; Putri Salehah Siregar (Pusat Riset dan Inovasi Nasional, 2025)
The education system in the United Kingdom has undergone significant development over time, encompassing primary, secondary, and higher education. Primary and secondary education is structured within a framework that ensures universal access and high standards, starting from mandatory education for children aged 5 to 16 years. Higher education in the UK is renowned for its quality, with prestigious universities focusing on research and professional development. Public policies, such as the Education Act of 1944 and the national curriculum introduced in 1988, have played a vital role in shaping and updating the education system. However, modern challenges such as social and economic disparities, inconsistent policy changes, and academic pressure and mental health issues among students remain ongoing concerns. With continued efforts to improve the education system, the UK continues to adapt to changes in time and global challenges.